Synthesis, DNA Binding Studies and Molecular Docking of Tetrahydroquinoline-3-Carbonitrile Derivatives - Pogaku, Bhadraiah; Karra, Amarender; Police, Vishnuvardhan Reddy; Damera, Thirupathi; Mone, Radhika (Current Organic Chemistry, 2025)
In this study, a series of 2-amino-4-(substituted phenyl)-5,6,7,8-tetrahydroquinoline -3-carbonitrile derivatives (<span class=
Keywords: multi-component